2011
DOI: 10.1189/jlb.0111020
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of theIL31gene by NFAT and STAT6

Abstract: IL-31, a newly identified member of the IL-6 cytokine family, is involved in many pathological conditions, including atopic dermatitis and pruritis. In this study, we investigated how expression of IL-31 is regulated in T cells and mast cells. We observed that expression of IL-31 required a calcium signal and was dependent on the calcineurin-NFAT signaling pathway. Moreover, we found that IL-31 promoter contains a positive regulatory region that mediates calcium- and IL-4-dependent induction of the IL-31 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Studying the promoter region of the IL31 gene Park et al identified IL-4-dependent STAT6 and calcium-dependent NFAT2 (NFATc1) and NFAT1 (NFATc2) binding sites which appear to act synergistically to enhance IL-31 expression in T H 2 lymphocytes and mast cells [125]. These transcription factor binding sites are evolutionary conserved.…”
Section: Transcription Biosynthesis and Secretion Of Il-31mentioning
confidence: 98%
“…Studying the promoter region of the IL31 gene Park et al identified IL-4-dependent STAT6 and calcium-dependent NFAT2 (NFATc1) and NFAT1 (NFATc2) binding sites which appear to act synergistically to enhance IL-31 expression in T H 2 lymphocytes and mast cells [125]. These transcription factor binding sites are evolutionary conserved.…”
Section: Transcription Biosynthesis and Secretion Of Il-31mentioning
confidence: 98%
“…Therefore, we decided to focus on the synergistic effect between NFAT1 and JunB for IL-31 gene expression. We also tested whether STAT6 could activate the mouse IL-31 promoter because STAT6 was reported as a key transcription factor for enhancing the human IL-31 promoter activity (24). Unlike in the human IL-31 promoter, NFAT2 and STAT6 failed to activate the mouse IL-31 promoter, and NFAT1 alone sufficiently activated the mouse IL-31 promoter in a STAT6-independent manner (Supplemental Fig.…”
Section: Functional Cooperation Between Nfat1 and Junb To Activate Ilmentioning
confidence: 99%
“…Genomic sequences spanning the IL-31 gene were analyzed using the Web-based alignment software VISTA browser 2.0 (23). Transcription factor binding sites were identified using the rVISTA 2.0 software (24), which uses matrices of the TRANSFAC database (25). Putative recognition sites for regulatory factors were also identified by searching the JASPAR database (26) and verified from previously reported literature.…”
Section: Computational Analysis Of the Conserved Nucleotide Sequence mentioning
confidence: 99%
“…Receptors for IL-13 and IgG are present on these cell types. Signals via signal transducer and activator of transcription 6 (STAT6, IL-13-receptor initiated) and nuclear factor of activated T cells (NFAT, IgG–Fc-receptor initiated) can for example function synergistically for inflammatory cytokine production [78]. Several lines of evidence indicate that NFAT signaling can contribute to the behavioral changes in endothelial cells and smooth muscle cells that cause pulmonary arterial remodeling and constriction then resulting in pulmonary hypertension [17, 79, 80].…”
Section: Discussionmentioning
confidence: 99%